Unusual laryngeal mass: when it’s not malignancy – a case of supraglottic Schwannoma - KC, Sudeep; Paneru, Manisha; Yadav, Deepak; Shrestha, Manisha (Journal of Patan Academy of Health Sciences, 2025)
Neurogenic tumors of the larynx are very rare, with laryngeal schwannomas making up about 0.1-0.3% of cases. Laryngeal schwannoma is a slow-growing, benign encapsulated, neurogenic tumor typically found in the supraglottic larynx, rarely in the glottis. This report discusses a 44-year-old female with a hoarseness of voice and dyspnea on exertion. Imaging findings were suggestive of benign lesion. Patient underwent Microlaryngeal Surgery (MLS) excision and was confirmed histologically as a Schwannoma. This report highlights this rare condition and reviews diagnostic methods, differential diagnoses, and treatment options.